Carlos Alberto Seguín Escobedo (1907-1995): A Peruvian as President of the Interamerican Society of Psychology - Arias Gallegos, Walter; Gallegos, Miguel; Caycho-Rodríguez, Tomás (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2021)
In this article we present the life and work of Carlos Alberto Seguín (1907-1995), a renowned Peruvian psychiatrist, who disseminated the psychological knowledge and supported the development of psychosomatic medicine in Latin America, offering pioneering ideas in fields of social psychiatry and in psychotherapy based on psychoanalytic and existentialist perspectives. We provided an overview of his early years as a psychiatrist and psychoanalyst, followed by a discussion of his contributions in various events and professional organizations including the Interamerican Society of Psychology. Furthermore, we examined his academic career, his work publishing in peer reviewed journals, and later as an Editor.